2018
DOI: 10.1021/acs.macromol.7b02315
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polymeric Nanocomposite Hydrogels Containing the Pendant ZnS Nanoparticles: Approach to Higher Refractive Index Optical Polymeric Nanocomposites

Abstract: Nanocomposites have attracted more attention due to their extensive applications. However, it is still a huge technological challenge in fabrication of transparent hybrid materials because of nanoparticle aggregation resulting from their high specific surface energies. In this paper polymerizable molecule was controlled chemically grafted onto ZnS nanoparticles to obtain polymerizable-group-capped nanoparticles that can copolymerize with a mixture of acrylic monomers of N,N-dimethyl­acrylamide (DMA) and 2-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
1
25
0
1
Order By: Relevance
“…TiO 2 -PHEMA hydrogel TiO 2 -PHEMA hydrogel (Tummala et al, 2016) ( Xu et al, 2018). Zhao et al, (2018) has suggested a ZnS-inorganic hydrogel CLs (Fig.…”
Section: Contact Lensmentioning
confidence: 99%
“…TiO 2 -PHEMA hydrogel TiO 2 -PHEMA hydrogel (Tummala et al, 2016) ( Xu et al, 2018). Zhao et al, (2018) has suggested a ZnS-inorganic hydrogel CLs (Fig.…”
Section: Contact Lensmentioning
confidence: 99%
“…For functional inorganic material/polymer nanocomposites, an elemental mapping with EDS is a powerful means to evaluate the homogeneity of the resulting composite materials [99][100][101][102][103][104][105][106]. Figure 14 shows the fabrication of high refractive index nanocomposite hydrogel by copolymerizing N,N-dimethyl acrylamide (DMA), 2-hydroxyethyl methacrylate (HEMA) or glycidyl methacrylate (GMA) or methyl methacrylate (MMA), and polymerizable methacrylate grafted on ZnS nanoparticle [107]. The properties of a hydrogel such as permeability, mechanical robustness, water content, and refractive index can be effectively controlled by simply varying the amount of ZnS capped with a polymerizable functional group.…”
Section: Energy-dispersive X-ray Spectroscopymentioning
confidence: 99%
“…NPs. Polymerizablegroup-capped ZnS was synthesized according to our previous route [17,18]. Briefly, ME-capped ZnS NPs (3 g) and one drop of DBTDL were dispersed in 75 mL DMF, in which DMF solution of 2-isocyanatoethyl methacrylate (0.3 g in 15 mL DMF) was added drop by drop in half an hour, and then, the solution was kept at 30°C for 2.5 h under continuous stirring and ultrasound.…”
Section: Polymerizable-group-capped Znsmentioning
confidence: 99%